Filosofi Keuangan Sosial Islam Produktif sebagai Instrumen Keadilan Distributif dalam Maqasid Syariah - Wardah Mujadidah Hananiyah; Asnaini; Desi Isnaini (Al-Muzdahir : Jurnal Ekonomi Syariah, 2026)
Islamic social finance is an essential component of the Islamic economic system that functions as an instrument for wealth redistribution, strengthening social solidarity, and promoting social welfare development. However, the management of Islamic social finance has largely remained charitable and consumptive in nature, limiting its effectiveness in creating sustainable economic empowerment. This study aims to analyze the transformation of productive Islamic social finance as an instrument of distributive justice from the perspective of maqasid sharia. This research employs a qualitative approach using a library research method through the analysis of relevant literature, including books, scientific journals, and previous studies related to Islamic social finance. The findings indicate that the transformation of Islamic social finance from a consumptive approach to a productive approach reflects the actualization of maqasid sharia in the economic field, particularly in preserving wealth (hifz al-mal), protecting human life (hifz al-nafs), and promoting public welfare (maslahah ‘ammah). Instruments such as zakat, infaq, sadaqah, waqf, hibah, and qurban function not only as philanthropic mechanisms but also as economic redistribution systems capable of encouraging community empowerment, strengthening micro and small enterprises, improving economic capacity, and supporting sustainable welfare development. This study also emphasizes that the integration among Islamic social finance instruments has significant potential to support a more just, inclusive, and sustainable economic development. Nevertheless, the implementation of productive Islamic social finance in Indonesia still faces several challenges, including weak institutional governance, low public literacy, and the lack of optimal integration among institutions and Islamic social finance instruments